Evaluación del impacto de los sedimentos en la planificación de los recursos hídricos. Caso de estudio: cuenca Campoalegre (2021)
Accelerated erosion in watersheds is increasingly evident around the world, this rise in sediment production is related to changes in land use and its poorly planned uses. In Colombia this is a complex challenge, as it is related to productive activity, poor public policies, and the culture of the population, generating degradation in the basins. The increase in the volume of sediments has different consequences in the water cycle, transforming its conditions and its use, being necessary to understand these new conditions in the planning of water resources. For evaluating the impact of sediments on water management, a hydro sedimentological modeling is proposed using the Tetis-Sed distributed model, in the Campoalegre river basin (Caldas, Risaralda). With the calibrated and validated model, different future scenarios were proposed, according to climatic and productive trends and the ideal scenario of land use, in which the variation in the solid flow was defined for each of them. Additionally, a planning tool is proposed that relates the impact of water use (demand) and sediment production through the Water Usage Index, one of the main planning indicators in Colombia. The work allows the use of modeling tools such as TETIS-SED with which a planning tool is proposed to avoid problems with water resources